Development of Student Literacy and Numeracy through Cultural Work on Making Karo Special Food at SD Negeri 040515 Tiga Jumpa, Karo Regency - Mian Siahaan; Dicho Niko Demus Sihombing; Tinadya Maya Sari Sinaga; Marnisa Tiurma Tampubolon; Devier Portina Malau; Sara Meylan Purba; Meilani Mutiara Sihaloho (Jurnal Pengabdian Masyarakat Bestari, 2023)
The purpose of this community service program is to improve students' literacy and numeracy skills through the cultural work of making Karo special food at SD Negeri 040515 Tiga Jumpa, Karo District. This program takes place from February 3–25, 2023, and involves all students from grades I–VI. The method used is to form groups of students who cannot read and guide them to understand the material that is not understood by doing additional tutoring. The results obtained through the activities of this community service program are increasing interest in reading, getting to know student numbers, and increasing students' insights about Karo culture. This program was declared successful because the results obtained met the expected goals and increased students' reading and numeracy skills, as evidenced by the increased scores on their daily assignments.